Sistema para evaluación de la espasticidad muscular - Schiaffino, L; Spaich, E; Rufiner, A; Escobar, S; Tabernig, C (Revista Mexicana de Ingenieria Biomedica, 2002)
Spasticity is a motor control disorder common in people with lesions in the central nervous system. To evaluate the effect of different rehabilitation treatments it is necessary to assess the level of spasticity. A system to evaluate the spasticity of the quadriceps muscle, before and after applying a treatment based on electrical stimulation, is described in this paper. The spasticity level is quantified through the normalized relaxation index (NRI), computed after performing the pendulum test. It is also assessed by the Ashworth scale and the patient opinion. The system consists of 3 blocks: a goniometer, a portable unit that records and transfers the data to the PC, and specific software. The entire system was used to evaluate 32 patients. Based on the experimental results, we can conclude that the system was robust and easy to operate in the hospital environment. Furthermore, the possibility of recording the evolution of spasticity levels, both qualitatively and quantitatively, offers a useful tool to study the effects of electrical stimulation on spasticity